Sosialisasi dan Pelatihan Digital Marketing Sebagai Upaya Pemasaran Produk UMKM di Desa Kebondalem - Ida Bagus Anindya Hariwicaksana; Wahyu Fahrul Ridho (Yayasan Daarul Huda Kruengmane, 2023)
One of the villages in Bareng District, Jombang Regency, which has quite a lot of MSMEs, is Kebondalem Village. MSME actors in Kebondalem Village have even increased every year. Most small, micro and medium enterprises (MSMEs) have a similar problem, which is that it is difficult for them to promote their business to the wider community. The purpose of this socialization is to increase knowledge of marketing and advertising media to increase the number of customers and to be known more widely. The implementation of this student service involves MSME partners who experience several problems related to the management and management of promotional media which are considered less effective. One of the work programs implemented is the application of digital marketing as an effort to market MSME products. Coinciding with this activity, students provide assistance and training related to the application of digital marketing for these MSMEs.